Negotiating Power: How youth organizers recast the debate about school reform. Issue 8 (25th November 2019) - Rosen, Sonia M.; Conner, Jerusha
Abstract: In the context of a neoliberal policy landscape, urban high school students who are constructed by policymakers as either dependents or deviants have little to no agency in the larger policy debates that shape what kinds of educational opportunities and choices are available to them. In this article, we explore how the Philadelphia Student Union (PSU), a youth organizing group, engaged in the debate around educational change and attempted to shift public opinion and understanding. Specifically, we examine how PSU derived and deployed power in a contest with school policymakers about educational reform. Understanding this exercise of power as a means of advancing youth voice and developing equitable systems of public accountability for all stakeholders can help us better appreciate the role youth can play in negotiating the terms of the debate over how best to improve the schools serving our nation's most vulnerable students.